Forms and Availability of K in the Medium Textured Alluvial Soils of Arid Rajasthan - Dutta, B K; Joshi, D C (Annals of Arid Zone, 2016)
The potential and available forms of potassium were studied in medium textured alluvial soils in south-eastern puts of arid Rajasthan. The soils had better contents of potential and available forms but the potassium saturation percentage was lower than that in the dune and interdunal soils. Correlation of soil parameters and multiple regression analyses with different forms of K revealed that various soil parameters better accounted for the variabilities in available forms than for the .potential forms of K. The dynamic relation between various forms has been discussed.